PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2016 - Fanny Melyana; Werner Ria Murhadi; Endang Ernawati (CALYPTRA, 2018)
This study aims to analyze the effect of working capital management on the profitability of company on the Indonesian Stock Exchange during the period 2012-2016. In order to know the relationship occur among the independent variable (number of days account receivable, number of days inventories, and number of days account payable) on Return of Assets using the multiple linear regression analysis model to analyze the data. The target population of this study are all non-financial companies registered in Indonesia Stock Exchange in 2012-2016 which are equal to 1335 observation. The control variables that were used in this study for measurement of working capital management are firm size, growth and financial debt (leverage). The research finds that number of days account receivables, number of days account payable, size, and debt affect profitability negatively. On other hand, growth affect profitability positively.